Analysis water content of Seawater Desalination Technology by Using Multistage Distillation - Hadi, Sofyan; Permadi, Adi; Maryudi; Syamsuddin, Arief; Fatwa Zufar , Ahmad (Indonesian Journal of Chemical Engineering, 2024)
Desalination technology, which has been the most widely utilized method of meeting the requirement for clean water for the past 50 years, can be employed in attempts to use seawater. The purpose of this study is to ascertain how variations in the composition of distilled water are affected by the multistage distillation of seawater from Cemara Sewu Beach, Bantul, Yogyakarta. LPG gas is used as fuel to heat sea water during the distillation process. To obtain distilled water, the seawater vapor is then condensed. Subsequently, the distillation procedure is executed in three phases, with every phase being evaluated using the distilled water. The overall CaCO3 hardness level in the first stage of distilled water is still high, thus it does not exceed clean water quality criteria. Meanwhile, in the second and third stages, there are two parameters, namely pH and total hardness level, which do not meet the clean water requirements. In general, the first stage of distilled water is sufficient to be processed into clean water with the addition of water hardness treatment. Repeated distillation has a tendency to reduce pH, total hardness, TDS, fluoride, nitrate and detergent.